Prognostic Significance Association of Neutrophil-To- Lymphocyte Ratio and Platelets-To-Lymphocyte Ratio with Mortality in COVID19 Patients - Hoda Elsayed Mohammed; Sama Mohammed N. Attiyah (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Inflammation is a key factor in COVID-19 progression and is potentially an importantpredictive factor. The ratios of neutrophils to lymphocytes and platelets to lymphocytes may showsignificant inflammatory progression, which may contribute to the development of some majorcomplications and mortality problems as observed in COVID-19. Objective: To examine and investigatethe correlation of neutrophil lymphocytic ratio (NLR) and platelets to lymphocytes ratio (PLR) withincreased mortality risk.Methods: 124 patients admitted to King Abdulaziz hospital with confirmed COVID-19 were enrolled inour study. The blood cell count was used to obtain NLR and PLR. The receiver operating characteristic(ROC) curve was used to determine the sensitivity and specificity of NLR and PLR for severity andmortality of admitted patients with COVID-19. The logistic regression model was used to explore therisk factors associated with mortality and severity.Results: The mortality rate was 23.4%. Among non-survivors’ patients’ lymphocyte significantlydeclined with 96.5%, while neutrophil counts increased. The Empirical optimal cut point of NLRcorrelated with mortality is 4.647, with a sensitivity of 93% and a specificity of 61% (AUC: 0.847, 95%CI 0.774-0.921; P = 0.001). Moreover, the optimal cut point of PLR associated mortality is 17.358,with a sensitivity of 90% and a specificity of 64% (AUC: 0.791, 95% CI 0.703-0.878; P = 0.005).Conclusions: NLR and PLR variables were significantly correlated with severity and mortality. NLRand PLR can be considered independent biomarkers in COVID-19 patients which play a significant roleto predict mortality cases.